Contribuição de empresas sociais baseadas em tecnologia da informação e comunicação para o desenvolvimento humano : uma abordagem de capacitações - Pereira, Daniel Lanes (2015)
Human Development through empowerment, participation and capability expansion has been in the center of United Nations and governments around the world. Also, civil society found different ways to help in human development with entrepreneur people who hope to do something to society. Social enterprises arose through self sustainable business models to create social value while helping individual capability expansion, according to the economist and philosopher Amartya Sen. Information and communication technology has been at the core of social enterprises business models, with a important hole at human development. This work confirms the contribution in creating social value of information and communication technology based social enterprises, using Amartya Sen´s capability approach, with a qualitative approach research at Saútil and Kiduca, social enterprises based in ICT.